Budaya Daur Hidup (Siklus Kehidupan) Suku Serawai Di Kabupaten Bengkulu Selatan - Dihamri Dihamri (Universitas Prof. Dr. Hazairin, S.H, 2017)
In South Bengkulu district of Bengkulu province, the majority of indigenous people are Serawai tribe. Serawai tribe is rich in culture, one of Serawai's cultural treasures is the culture of life cycle. Culture is due to the development of the eroded began to exist even disappeared. General research is to preserve the culture of Serawai tribe. The specific purpose of this research is to describe the life cycle culture of Serawai tribe that still exist in the life of the Serawai people. The research method is qualitative. Research location of South Bengkulu district. Primary data sources are informants and also use secondary data. Data collection techniques are: in-depth interviews, documentation and observation. Analyze data from beginning to end. The result of research is found culture of life cycle are: culture of birthing, beterang (circumcision of woman), male circumcision, association of youth, marriage and death. The culture has started to change and some tend to disappear. The government and society are still working to preserve it.